Effects of including gender and multicultural course content on classroom dynamics in adult higher education classes: A qualitative study of faculty perspectives - Elizabeth J. Tisdell; Sylvia McLaurin (Adult Education Research Conference, 1994)
This qualitative study examined how instructors who include gender and multicultural course content view the effects of the inclusion of those issues on the classroom dynamics in their classes.